Oligovalent Fab Display on M13 Phage Improved by Directed Evolution - Huovinen T; Sanmark H; Yla-Pelto J; Vehniainen M; Lamminmaki U (HUMANA PRESS INC, 2022)
Efficient display of antibody on filamentous phage M13 coat is crucial for successful biopanning selections. We applied a directed evolution strategy to improve the oligovalent display of a poorly behaving Fab fragment fused to phage gene-3 for minor coat protein (g3p). The Fab displaying clones were enriched from a randomly mutated Fab gene library with polyclonal anti-mouse IgG antibodies. Contribution of each mutation to the improved phenotype of one selected mutant was studied. It was found out that two point mutations had significant contribution to the display efficiency of Fab clones superinfected with hyperphage. The most dramatic effect was connected to a start codon mutation, from AUG to GUG, of the PelB signal sequence preceding the heavy chain. The clone carrying this mutation, FabM(GUG), displayed Fab 19-fold better and yielded twofold higher phage titers than the original Fab.